Kerentanan dalam Psikologi Forensik - Pacciolla, Aureliano (ANIMA Indonesian Psychological Journal, 2026)
This article aims to initiate a discussion among psychologists and lawyers on the concept of vulnerability in forensic psychology to facilitate its application to current legislation. After considering in general the concept of vulnerability in contemporary forensic psychology, starting with the original meaning of fragility or vulnerability and going on to mention the most credible contemporary authors on this point, (§ 1) the author will consider the vulnerable victim as described in the most accredited definitions of official victim protection documents. (§ 2) More specifically, vulnerability will be dealt with in sexual offences, along with some historical aspects, and the specifics of child maltreatment: intrafamilial and extrafamilial. (§ 3) Special attention will be given to the complexity of diagnosis in the context of forensic psychology: vulnerability in the most relevant syndromes according to the DSM-5. (§ 4) A very specific aspect of the definition and application of vulnerability is in the context of the Catholic ecclesiastical court, which, as in other forensic contexts, is still being redefined for the consideration of various crimes, but also for the establishment of safeguarding committees. (§ 5) A very important part has been reserved for proposals (§ 6) of three practical tools for vulnerability assessment and diagnosis that forensic psychologists can use on a case-by-case basis. In the conclusion, the limits of this study on vulnerability are indicated, and the training of practitioners is encouraged to identify the correlations between clinical and legal criteria in the context of Logotherapy as the point of reference of the Existential-Humanistic approach.